Seroprevalence of caprine artritis-encephalitis virus in goats of Lima region, Peru - Gomes M., Angel (2015)
The seroprevalence of caprine artritis-encephalitis virus (CAEV) in four provinces of Lima Region, Peru was determined in 381 goat serum samples (325 females and 56 males) older than 12 months from 89 flocks reared under intensive (n=3), semiextensive (n=49) and transhumant (n=46) production systems. The detection of antibodies against CAEV was done by a competitive-inhibition ELISA test. The overall seroprevalence of CAEV was 0.26 ± 0.09% (1/381). The seropositive goat belonged to one flock from Huaral district. The serology of all animals older than 12 months in this flock resulted in other nine seropositive goats. The 10 animals were clinically normal and represented 9.7% (10/ 103) of seroprevalence of CAEV in the flock. All bucks were negative. The results indicate that CAEV has a low seroprevalence in goats in Lima.